2015
DOI: 10.1002/bit.25860
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and predicting carboxylic acid reductase activity for diversifying bioaldehyde production

Abstract: Chemicals with aldehyde moieties are useful in the synthesis of polymerization reagents, pharmaceuticals, pesticides, flavors, and fragrances because of their high reactivity. However, chemical synthesis of aldehydes from carboxylic acids has unfavorable thermodynamics and limited specificity. Enzymatically catalyzed reductive bioaldehyde synthesis is an attractive route that overcomes unfavorable thermodynamics by ATP hydrolysis in ambient, aqueous conditions. Carboxylic acid reductases (Cars) are particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Controls with all potential by‐products showed that the precipitate was pyrophosphate. Consistent with the observations from the Prather group with Ni CAR,11 these results indicate the inhibition of Nc CAR by the co‐product pyrophosphate. An experiment including pyrophosphatase showed that the concentration of 1b can indeed be increased‐two fold in vitro (Supporting Information, Figured S4).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Controls with all potential by‐products showed that the precipitate was pyrophosphate. Consistent with the observations from the Prather group with Ni CAR,11 these results indicate the inhibition of Nc CAR by the co‐product pyrophosphate. An experiment including pyrophosphatase showed that the concentration of 1b can indeed be increased‐two fold in vitro (Supporting Information, Figured S4).…”
Section: Resultssupporting
confidence: 90%
“…The hit with highest scores was a hypothetical protein with NCBI accession code XP_955820.1. On the sequence level, this protein showed low identities with the original search templates Ni CAR, Mm CAR, Sr CAR and At CAR (17.3%, 17.5%, 18.5% and 22.5%, respectively), and also low identities with CARs that have been published during this study: Mn CAR,9 Tv CAR,10 Ms CAR,11 Nb CAR11 and Sb CAR12 (16.4%, 26.1%, 17.7%, 17.3% and 22.4%, respectively). A codon optimized synthetic gene coding for XP_955820.1 from N. crassa OR74A was expressed with an N ‐terminal TEV cleavable HIS‐tag from the multiple cloning site 2 of the pETDUET1 vector.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Of specific interest were amine nucleophiles that would lead to amide bond formation from acid and amine,an important challenge in organic chemistry. [8] Thea ctivated substrate is then attacked by the thiol of the enzyme-bound PPant group,generating athioester intermediate that is transferred to the reduction domain. CARs are composed of three distinct protein domains:t he adenylation domain, which itself is divided into ac ore-domain and subdomain, [7] the peptidyl carrier protein with the bound 4'-phosphopantetheine (PPant) prosthetic group,and areductase domain.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that substrates with an amine group at the α-position are scarcely accepted by carboxylic acid reductases [48], suggesting that production of ( S )-2-aminobutanol may be further boosted by optimizing the substrate binding site of the carboxylic acid reductase.…”
Section: Discussionmentioning
confidence: 99%